The Telenovela and the Representation of Black Women: A Study from the Controlling Images Analytical Category - Effgen Santos, Matheus (2023)
In Brazil, the telenovela has established itself as one of the most important products of television. Thus, it addresses the differences between social groups and disputes between them. The visibility for these groups that is built from this dynamic becomes a chance to promote their representation, when they see themselves as part of the nation. This study aims to understand the representation of Black women in the scenario of contemporary Brazilian telenovelas, focusing on Amor de Mãe (Dias & Villamarim, 2019–2021). The research consisted of analyzing the protagonists of the first part of this narrative, Camila (Jéssica Ellen) and Vitória (Taís Araújo), based on the analytical category of controlling images (Collins, 1990/2019), which unravels the logic that tries to justify the oppression experienced by these women. The results show that these images can be identified isolated and/or combined in the construction of these characters. At times, the telenovela plot questions these images; at others, it reinforces them.